Condições de existência do sujeito surdo: os efeitos discursivos de língua, cultura e comunidade nos modos de vida contemporânea - Gomes, Anie Pereira Goularte (2020)
This thesis was produced at the Education Graduate Program at the Federal University of Santa Maria (PPGE/UFSM), under the Special Education, Inclusion and Difference Research Line. Its main objective is to understand the current functioning of the discursive network that leads and regulates the ways of life of deaf subjects. The analytical corpus of the research was composed by the statements of the discursive matrix on language, culture and community arising from a bricolage exercise with different activities carried out with six groups of deaf subjects. These activities sought the following objectives: to identify a constitutive factor in deaf narratives of the languages in contact; to problematize the relationship of cultural appropriation and belonging in the processes of subjectification; and to analyze the effects of discursive formation about a community in the deaf subjects' ways of life nowadays. From the materiality produced, the analysis considered the conditions of existence of the deaf subjects, in which it was possible to perceive the metanarratives that constitute the archive - Foucault's concept - that encompasses contemporary discursive practices and leads deaf people’s lives. In this sense, we sought to unveil the concept of archive, since from this study, we identify a discursive formation with a fixed position of a shut up deaf subject based on an essence of the deaf individual. However, this position showed some ruptures and discontinuities that instituted other ways of being/living/existing as a deaf person, which constitute a possible new discursive archive. This study showed certain discursive recurrences about language, culture and community that are sometimes more plastered. On the other hand, they become more fluid and may leak and flow in a way to constitute a more liquid and discontinuous discourse formation that is capable of tensioning the great truths produced around the deaf subject. These movements of rupture with the discursive matrix have been producing another knowledge that endorses the ways of life of the deaf community. This discussion made it possible to see that enunciative mismatches may lead to other life approaches that, in the context of this thesis, can be understood as an unholy citizenship, once it escapes what is considered sacred in the local community. Thus, one of the possible effects of this profane citizenship referred, in the context of this thesis, to the concept of Larrosa's experience, for in it (profane citizenship) the irrevocable truths that capture and annihilate the event become more distant and the re-existence emerges as an inventive creation through experience. This thesis contributes to the hypercritical trend towards the proliferation of more doctrinal discourses on the conditions of the deaf existence. By converting the deaf existence into an experience to escape the essence given by the community, the pieces of the discursive mosaic have been gaining new colors and textures in what regards the deaf subject marked by a singular form of being/being/existing.